2018
DOI: 10.2147/ppa.s185129
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of and willingness to pay for using a smartphone-based vaccination application in a Vietnamese cohort

Abstract: BackgroundThe increasing accessibility of smartphone in Vietnam shows potential in using smartphone applications for vaccination management to improve compliance. However, the acceptability and financial feasibility of using this application in Vietnam have not yet been understood. This study measured the general perception of and willingness to pay (WTP) for using smartphone-based vaccination management applications and their associated factors in Vietnam.Subjects and methodsA cross-sectional study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Our findings confirmed the potential for the use of mHealth in assisting patients' treatment adherence in resource-limited settings [22][23][24]. In the context of Vietnam, a small percentage of respondents who were using health-related apps was comparable to that of a survey on smartphone-based vaccination application (5%) [25]. However, the proportion of participants willing to pay for an app in this study was higher than the previous studies related to vaccination (79.1%) [25], ART adherence support (63.5%) [15], and smoking cessation (26.8%) [26].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our findings confirmed the potential for the use of mHealth in assisting patients' treatment adherence in resource-limited settings [22][23][24]. In the context of Vietnam, a small percentage of respondents who were using health-related apps was comparable to that of a survey on smartphone-based vaccination application (5%) [25]. However, the proportion of participants willing to pay for an app in this study was higher than the previous studies related to vaccination (79.1%) [25], ART adherence support (63.5%) [15], and smoking cessation (26.8%) [26].…”
Section: Discussionsupporting
confidence: 78%
“…In the context of Vietnam, a small percentage of respondents who were using health-related apps was comparable to that of a survey on smartphone-based vaccination application (5%) [25]. However, the proportion of participants willing to pay for an app in this study was higher than the previous studies related to vaccination (79.1%) [25], ART adherence support (63.5%) [15], and smoking cessation (26.8%) [26]. Regarding the amount of money, the average amount for WTP found in this study was higher than that reported in a prior ART adherence-support application (VND 51,000 or United States dollar (USD) 2.5 per month) [15].…”
Section: Discussionmentioning
confidence: 65%
“…Six studies intended to improve health behavior changes, including treatment adherence [13,14], mental health care [15], and smoking cessation [11,12,16]. Eight studies intended to improve healthcare services, including medical records management [17], health monitoring and support [9,18,19], vaccination management [10], patient-provider communication [8], and follow-up care [20,21].…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…This method is a standard and accepted technique of stated preferences for capturing maximum WTP and was originally developed as a method for valuing environmental benefits. 25,[36][37][38] It includes 2 steps. First, the outlining of the efficacy of hypothetical vaccine was estimated with an efficacy rate of about 99%.…”
Section: Contingent Valuation Approachmentioning
confidence: 99%